Ramadan fasting reduces high-sensitivity C-reactive protein among HIV-infected patients receiving antiretroviral therapy - Widhani, Alvina; Yunihastuti, Evy; Setiati, Siti; Witjaksono, Fiastuti; Karjadi, Teguh H. (Frontiers in Nutrition, 2023)
Background: Inflammatory conditions and oxidative stress increase in HIV infection, and inflammation increases the risk of cardiovascular disease. Ramadan fasting is known to reduce inflammation and oxidative stress in diabetic patients. This study examined the effects of Ramadan fasting on high-sensitivity C-reactive protein (hs-CRP) levels and total antioxidant status (TAOS) in HIV patients on antiretroviral therapy (ART). Methods: This was a prospective cohort study comparing HIV-infected patients on stable ART who observed Ramadan fasting with non-fasting HIV-infected patients. Inclusion criteria were men aged 20–40 years, taking first-line ART for at least 6 months, Muslims intent to fast for Ramadan, no current hospitalization because of acute conditions and not being treated for opportunistic infections. Results: After 2 weeks, hs-CRP had decreased significantly in the fasting group (-0.41 mg/L [IQR = -1; 0.10]) compared to the non-fasting group (0.20 mg/L [IQR = -0.30; 1.50]) (p = 0.004). The linear regression analysis has shown that Ramadan fasting contributed to 10.10% of the variance in hs-CRP value (R2 = 0.101) and decreased its value by 0.317 points (B = -0.317). Changes in TAOS did not significantly different (p = 0.405) between the fasting group (0.05 mmol/L [IQR = -0.03; 0.12]) and the non-fasting group (0.04 mmol/L [IQR = -0.13; 0.36]). In the fasting group, there were significant changes in polyunsaturated fatty acid consumption (p = 0.029), body weight (p = 0.001), cigarette smoking (p = 0.001), and sleeping duration (p = 0.001). Conclusion: Ramadan fasting reduces hs-CRP concentrations among HIV patients on ART.